Human Albumin Fragments Nanoparticles as PTX Carrier for Improved Anti-cancer Efficacy - Ge, Liang; You, Xinru; Huang, Jun; Chen, Yuejian; Chen, Li; Zhu, Ying; Zhang, Yuan; Liu, Xiqiang; Wu, Jun; Hai, Qian (Frontiers in Pharmacology, 2018)
In this study, human serum albumin fragments (HSAF) nanoparticles (NPs) were developed as paclitaxel (PTX) carrier for enhanced anti-cancer performance. Human albumins were broken into fragments via degradation and crosslinked by genipin to form HSAF NPs for better biocompatibility, improved PTX drug loading and sustained drug release. Compared with crosslinked human serum albumin (HSA) NPs, the HSAF-NPs showed relative smaller particle size, higher drug loading, and improved sustained release. In vitro and in vivo results both indicated that the PTX loaded HSAF-NPs have shown good anti-cancer performance. And the anticancer results confirmed that NPs with fast cellular internalization showed better tumor inhibition. These findings will not only provide a safe and robust drug delivery NP platform for cancer therapy, but also offer fundamental information for the optimal design of albumin based NPs.